Adaptive Research with and without a Learning Alliance in Myanmar: Differences in learning process and agenda for participatory research. (1st June 2017) - Flor, Rica Joy; Maat, Harro; Leeuwis, Cees; Singleton, Grant; Gummert, Martin
Highlights: Adaptive Research and Learning Alliances have complementary value. Skill development and reconfiguration of practice are central in situated learning. Stakeholder participation should be guided by the unfolding of experiments. Functional linkages between practices are crucial in participatory innovation. Abstract: The main challenge for researchers and project staff when implementing inclusive approaches in agricultural innovation is how learning and technology adaptation interact and how to reach jointly set targets. We provide a comparative analysis of the learning process induced by adaptive research (AR) in one case and a combined AR with Learning Alliance (LA) approach in another. The AR approach bridged farmers and researchers, but its implementation where researchers controlled experimentation, was not optimally conducive to experiential and discovery learning. The combined AR and LA approach expanded the number of stakeholders with whom farmers interact. This broadened the learning agenda beyond the initial objectives of the project. Although a LA provided added value in increasing the scope for learning with other stakeholders, limitations also emerged from the autonomy and informality of the learning process. Our analysis, based on the notion of situated learning, revealed practical concerns were a major driver in the participatory process. Incorporating insights and skills developed from experimentation to support the reconfiguration of practices, not only farming but also trading and milling, is needed. Lastly, the approaches have complementary value. Inclusion of more actors, as in a LA should not merely facilitate deliberations between actors but also support the reconfiguration of different practices and the functional linkages between these practices.